Geospatial mapping of groundwater potential for irrigated agriculture in semi-arid Kongwa District, Central Tanzania - Zacharia, Faida; Nobert, Joel; Liwenga, Emma (Frontiers in Water, 2025)
Groundwater is vital for agriculture in semi-arid regions like Kongwa District, where surface water is scarce and rainfall unstable. Despite its significance, detailed knowledge on groundwater distribution in such areas is often lacking, hindering effective irrigation planning and sustainable water management. This study, therefore, unleashes that hidden potential by applying Geographic Information Systems and the Analytical Hierarchy Process to map groundwater potential zones for irrigation in Kongwa District. Seven thematic layers were selected including geology, slope, drainage, rainfall, soils, land use, and lineament density for Groundwater potential analysis. Parameters were weighed and determined using AHP and ranked based on their contribution to groundwater potential by expert. The resulting weighted layers were then aggregated in ArcGIS 10.5 through the Weighted Linear Combination (WLC) technique to generate the final groundwater potential map of Kongwa District. Data from 35 boreholes records were collected to determine the model precision and model validation and hydrogeological dataset were used to map ground water potential. The results indicated three zone of groundwater potential namely, high (32%), moderate (45%) and poor (23%) groundwater potential zones. The high groundwater potential zone is concentrated in the western and Southwestern parts of Kongwa District. The middle and northern areas of the district, indicate moderate groundwater potential. Conversely, areas with poor groundwater potential are predominantly located in the eastern and southeastern parts of the district. Validation of Groundwater Potential Zones generated through the AHP–GIS model, the study utilized both secondary hydrogeological data and community-based perceptions. Secondary data including records of borehole yields, well depths, and groundwater level measurements from 2010 to 2022. These datasets provided quantitative evidence on groundwater availability and distribution across the district. The findings offer both academic and practical value. They support the use of geospatial tools for effective groundwater assessment and provide a framework for policymakers, planners, and farmers to make informed decisions about irrigation development, climate resilience, and land use in semi-arid regions of Tanzania.